Cow's Milk Consumption and Health: A Health Professional's Guide. (3rd April 2019) - Marangoni, Franca; Pellegrino, Luisa; Verduci, Elvira; Ghiselli, Andrea; Bernabei, Roberto; Calvani, Riccardo; Cetin, Irene; Giampietro, Michelangelo; Perticone, Francesco; Piretta, Luca; Giacco, Rosalba; La Vecchia, Carlo; et al.
Abstract: The most recent scientific evidence supports the consumption of cow's milk and dairy products as part of a balanced diet. However, these days, the public and practicing physicans are exposed to a stream of inconsistent (and often misleading) information regarding the relationship between cow's milk intake and health in the lay press and in the media. The purpose of this article, in this context, is to facilitate doctor–patient communication on this topic, providing physicians with a series of structured answers to frequently asked patient questions. The answers range from milk and milk-derived products' nutritional function across the life span, to their relationship with diseases such as osteoporosis and cancer, to lactose intolerance and milk allergy, and have been prepared by a panel of experts from the Italian medical and nutritional scientific community. When consumed according to appropriate national guidelines, milk and its derivatives contribute essential micro- and macronutrients to the diet, especially in infancy and childhood where bone mass growth is in a critical phase. Furthermore, preliminary evidence suggests potentially protective effects of milk against overweight, obesity, diabetes, and cardiovascular disease, while no clear data suggest a significant association between milk intake and cancer. Overall, current scientific literature suggests that an appropriate consumption of milk and its derivatives, according to available nutritional guidelines, may be beneficial across all age groups, with the exception of specific medical conditions such as lactose intolerance or milk protein allergy. Key teaching points: Milk and its derivatives contribute essential micro and macronutrients to the diet, when consumed according to appropriate national guidelines, especially in infancy and childhood where bone mass growth is in a critical phase. Preliminary evidence suggests potentially protective effects of milk against overweight, obesity, diabetes and cardiovascular disease No clear data are available about the association between milk intake and cancer. Current scientific literature suggests that an appropriate consumption of milk and its derivatives may be beneficial at all ages, with the exception of specific medical conditions such as lactose intolerance or milk protein allergy.